Extracellular Vesicles and Their Applications in Tumor Diagnostics and Immunotherapy - Scott Strum; Valentina Evdokimova; Laszlo Radvanyi; Anna Spreafico (Cells)
Extracellular vesicles (EVs) are cell-derived nanoparticles that have attracted significant attention in the investigation of human health and disease, including cancer biology and its clinical management. Concerning cancer, EVs have been shown to influence numerous aspects of oncogenesis, including tumor proliferation and metastasis. EVs can augment the immune system and have been implicated in virtually all aspects of innate and adaptive immunity. With immunotherapy changing the landscape of cancer treatment across multiple disease sites, it is paramount to understand their mechanisms of action and to further improve upon their efficacy. Despite a rapidly growing body of evidence supporting of the utility of EVs in cancer diagnostics and therapeutics, their application in clinical trials involving solid tumors and immunotherapy remains limited. To date, relatively few trials are known to incorporate EVs in this context, mainly employing them as biomarkers. To help address this gap, this review summarizes known applications of EVs in clinical trials and provides a brief overview of the roles that EVs play in cancer biology, immunology, and their proposed implications in immunotherapy. The impetus to leverage EVs in future clinical trials and correlative studies is crucial, as they are ideally positioned to synergize with advancements in multi-omics research to further therapeutic discovery and our understanding of cancer biology.